Low-warpage POK material as well as preparation method and application thereof

By adding flat glass fiber and calcium sulfate whiskers to the POK material and combining other additives, a low warpage POK material is prepared, which solves the problem of warping and water absorption of gearbox shell materials in high temperature environments and improves mechanical performance and stability, suitable for cleaning the preparation of home appliance gearbox housing.

CN119264640APending Publication Date: 2025-01-07SUZHOU WODF NEW MATERIAL TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411510303.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing cleaning appliance gearbox shell materials are prone to warping in high temperature environments and have high requirements for long-term use of mechanical properties and chemical resistance, but the anti-warping effect of commonly used PBT/glass fiber or nylon/glass fiber composites Limited, and nylon material absorbs severe water.

Method used

Using low warping POK material, the ratio is adjusted by adding flat glass fiber and calcium sulfate whiskers to the POK resin, and combining coupling agent, antioxidant, lubricant, heat stabilizer and other components, twin screw extrusion is used. The machine is melt-kneaded and prepared to form a material with low warpage.

Benefits of technology

On the basis of not damaging the wear resistance, chemical resistance and hydrolysis resistance of POK materials, the comprehensive mechanical properties and warpage resistance of the material are significantly improved, mechanical strength and structural stability are improved, and service life is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005105272420000111
    Figure BDA0005105272420000111
  • Figure BDA0005105272420000121
    Figure BDA0005105272420000121
  • Figure BDA0005105272420000131
    Figure BDA0005105272420000131
Patent Text Reader

Abstract

The invention discloses a low-warpage POK material as well as a preparation method and application thereof, and relates to the technical field of modified polymer composite materials. The low-warpage POK material disclosed by the invention is prepared from the following components: 40 to 64 parts of POK resin, 0.1 to 0.5 part of a coupling agent, 0.05 to 0.5 part of an antioxidant, 0.5 to 5 parts of a lubricating agent, 0.01 to 5 parts of a heat stabilizer, 29 to 31 parts of glass fiber, 12 to 17 parts of mineral filler and 0.5 to 1 part of an anti-UV (Ultraviolet) agent, wherein the glass fibers comprise flat glass fibers, and the mineral filler comprises calcium sulfate whiskers. The material with the lowest warping degree is obtained by adjusting the ratio of the flat glass fibers to the mineral filler, and the comprehensive performance and the warping resistance of the POK material are greatly improved on the basis that the original wear resistance, chemical resistance and hydrolysis resistance of the POK material are not damaged. The preparation method disclosed by the invention is simple and easy to operate, low in preparation cost and suitable for being vigorously popularized in preparation of gearbox shells for cleaning household appliances.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of modified polymer composite materials, and in particular to a low-warpage POK material and a preparation method and application thereof. Background Art

[0002] POK (polyketone material) is a new type of polymer material whose main molecular chain is formed by carbon and hydrogen through high crystallization to form a dense crystalline structure. The unique molecular structure determines that POK has excellent oil resistance and chemical resistance. At the same time, POK resin has high impact strength, low water absorption, good processing performance, and can be used for a long time in an environment of 120°C. Therefore, POK has a very broad application prospect in the field of cleaning appliances.

[0003] For the gearbox housing of cleaning appliances, because it needs to protect the gears and motors, and has good tolerance to the external environment, solvents and internal lubricating oil corrosion, the gearbox housing needs to have extremely high mechanical properties, dimensional stability and chemical resistance. In addition, the gearbox housing has a large structural size and a complex product structure, which is prone to warping. At present, the gearbox housing parts of cleaning appliances are mostly made of PBT / 30% glass fiber or nylon / 30% glass fiber composite materials, because the glass fiber will be oriented during the injection molding process, resulting in a large difference in shrinkage rate between the flow direction and the vertical direction, resulting in a limited anti-warping effect. At the same time, the gearbox housing has high reliability requirements for long-term use, and the nylon material absorbs water more seriously.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] The object of the present invention is to provide a low-warpage POK material and a preparation method and application thereof, so as to solve the above-mentioned technical problems.

[0006] The present invention is achieved in that:

[0007] In a first aspect, an embodiment of the present invention provides a low-warpage POK material, which comprises the following components by weight:

[0008] POK resin 40-64 parts, coupling agent 0.1-0.5 parts, antioxidant 0.05-0.5 parts, lubricant 0.5-5 parts, heat stabilizer 0.01-5 parts, glass fiber 29-31 parts, mineral filler 9-20 parts, anti-UV agent 0.5-1 parts;

[0009] The glass fiber includes flat glass fiber; and the mineral filler includes calcium sulfate whisker.

[0010] In a second aspect, an embodiment of the present invention provides a method for preparing the aforementioned low-warpage POK material, the preparation method comprising:

[0011] POK resin, coupling agent, antioxidant, anti-UV agent, lubricant and heat stabilizer are mixed in a mixer at a reaction temperature of 40° C. to 80° C. for a reaction time of 1 min to 60 min to obtain a first blend;

[0012] The first blend, glass fiber and mineral filler are fed into a twin-screw extruder from a feeding port. The temperature of the twin-screw extruder is 100° C.-250° C. and the rotation speed is 250 rpm-400 rpm. After melt mixing, the mixture is extruded, pelletized and dried to obtain a low-warpage POK material.

[0013] In a third aspect, an embodiment of the present invention provides the use of the low-warpage POK material as described above or the low-warpage POK material prepared by the preparation method as described above in the preparation of a gearbox housing.

[0014] The present invention has the following beneficial effects:

[0015] The low-warpage POK material provided by the present invention, and its preparation method and application, add a composite ratio of flat glass fiber and calcium sulfate whisker to the POK material system, and adjust the ratio of glass fiber to mineral filler to obtain a material with the lowest warpage, which greatly improves the comprehensive performance and anti-warpage performance of POK without destroying the original wear resistance, chemical resistance and hydrolysis resistance of POK. The preparation method is simple and easy to operate, and the preparation cost is low, which is suitable for promotion in the preparation of gear box housings for cleaning household appliances. DETAILED DESCRIPTION

[0016] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0017] In a first aspect, an embodiment of the present invention provides a low-warpage POK material, which comprises the following components by weight:

[0018] 40-64 parts of POK resin, 0.1-0.5 parts of coupling agent, 0.05-0.5 parts of antioxidant, 0.5-5 parts of lubricant, 0.01-5 parts of heat stabilizer, 29-31 parts of glass fiber, 9-20 parts of mineral filler, 0.5-1 parts of anti-UV agent; wherein the glass fiber includes flat glass fiber; the mineral filler includes calcium sulfate whisker.

[0019] It should be noted that glass fiber has the characteristics of good insulation, strong heat resistance, good corrosion resistance, and high mechanical strength, but its disadvantages are brittleness and poor wear resistance. Commonly used PBT / glass fiber or nylon / glass fiber composite materials have limited anti-warping effects because conventional glass fiber will be oriented during injection molding, resulting in a large difference in shrinkage between the flow direction and the vertical direction. Flat glass fibers tend to flow in a planar state, which optimizes the thermoplastic processing process by reducing resin shear, providing better fluidity (increasing spiral flow), reducing friction and viscosity, and reducing fiber entanglement and breakage, helping to enhance the strength and rigidity of the material. In addition, flat glass fibers have a higher specific strength, that is, the force that a unit mass of material can withstand is large, which has an enhancing effect on the performance of POK materials.

[0020] Furthermore, the amount of glass fiber used is 30 parts.

[0021] Calcium sulfate whiskers in mineral fillers, with the following specifications: CaSO 4 Content>98%, diameter 1μm-4μm, average length 40μm-100μm, bulk density 0.45g / cm 3 -0.7g / cm 3 In other embodiments of the present invention, the specifications of the calcium sulfate whiskers can be reasonably adjusted according to actual needs.

[0022] Furthermore, the amount of the mineral filler is 12-17 parts.

[0023] In the embodiment of the present invention, special-shaped glass fiber-flat glass fiber is added to the POK material component, and the composite ratio of the special-shaped glass fiber and the mineral filler-calcium sulfate whisker is adjusted to obtain a material with low warpage. Without destroying the original wear resistance, chemical resistance and hydrolysis resistance of POK, the comprehensive mechanical properties and anti-warpage performance of POK are greatly improved.

[0024] It should be noted that warpage is an important indicator to measure the bending performance of materials. Specifically, warpage describes the degree of bending of a plane in three-dimensional space, which is usually caused by factors such as stress, thermal expansion and contraction or humidity changes inside the material.

[0025] Materials with low warpage have the following characteristics: they are not easily deformed when subjected to force and can maintain a relatively stable structural form, thereby improving the structural stability of the material; less stress accumulates inside the material, thereby enhancing the mechanical strength of the material and reducing the material's fragility; it helps to maintain the integrity of the lattice structure, thereby improving the transmission efficiency of electrons in the material, that is, the electron mobility; the material has a complete lattice structure and a high thermal conductivity efficiency, which helps the material dissipate heat in high temperature environments; it maintains the material's absorption, emission and transmission efficiency of light, thereby improving optical properties.

[0026] Materials with high warping will increase the risk of material failure or shorten their service life; reduce the mechanical strength of the material, making it more vulnerable to damage from external forces; cause the lattice structure to deform, affecting the transmission efficiency of electrons, that is, reducing electron mobility; the material lattice structure is destroyed and the thermal conductivity efficiency is reduced, which may lead to a decrease in the material's heat dissipation ability in a high temperature environment; the material's absorption, emission and transmission efficiency of light will be reduced, thereby reducing the optical performance.

[0027] Therefore, a material with low warpage was prepared, which not only enhanced the material performance but also expanded its application scenarios.

[0028] Furthermore, the ratio of glass fiber to mineral filler is 30:(12-17) by mass.

[0029] In an optional embodiment of the present invention, the POK resin is a mixed resin; the POK resin includes a high viscosity resin and a low viscosity resin in a mass ratio of 1:(1.5-2); further, the POK resin includes a high viscosity resin and a low viscosity resin in a mass ratio of 1:(1.7-2); further, the molecular weight of the high viscosity resin is 170000-190000, and the molecular weight of the low viscosity resin is 120000-140000.

[0030] It should be noted that high-viscosity POK resins usually have better wear resistance, chemical resistance and creep resistance, and are suitable for applications that need to withstand high loads or harsh environments; low-viscosity POK resins usually have better fluidity, are easy to process and shape, and are suitable for applications that require rapid molding or complex shapes; the present invention adjusts the reasonable ratio and mixes high-viscosity and low-viscosity POK resins, which can achieve dual optimization of POK material performance and efficiency, thereby improving the performance of the final product.

[0031] Specifically, in the embodiment of the present invention, the specific brand of the high viscosity resin is M330F produced by the Hyosung Group of South Korea, and the specific brand of the low viscosity resin is M930F produced by the Hyosung Group of South Korea. In other embodiments of the present invention, the specific brand of the resin and the usage ratio can be reasonably adjusted according to actual needs.

[0032] In an optional embodiment of the present invention, the coupling agent is selected from any one of N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane and γ-aminopropyltriethoxysilane.

[0033] It should be noted that coupling agent is a kind of organosilicon compound with special structure. The addition of coupling agent can increase the viscosity of the product and improve its viscosity. In its molecule, there are reactive groups that can combine with inorganic materials (such as glass, cement, metal, etc.) and reactive groups that can combine with organic materials (such as synthetic resin, etc.). Coupling agent is used as a surface modifier to improve the dispersibility and adhesion of plastics when it is filled with inorganic fillers. Coupling agent can not only increase the quality of plastics and reduce the cost of products, but also improve certain properties of plastic products.

[0034] If the amount of coupling agent added is too high, the product viscosity will be too high, affecting the use and dilution effect; secondly, it will cause the product color to change and affect the product quality and safety. If the amount of coupling agent used is too low, its effect cannot be maximized and the performance of the product will also decrease. In addition, the coupling agent needs to be mixed evenly with the other raw materials, otherwise the effect will decrease due to incomplete coating.

[0035] In an optional embodiment of the present invention, the antioxidant is selected from at least one of antioxidant 1010, antioxidant 1098, antioxidant 168, antioxidant 9228, antioxidant 2450, antioxidant AO-80 and MD-697; further, the antioxidant includes antioxidant 1010 and antioxidant 168 in a mass ratio of 1:2.

[0036] Antioxidants, also known as antioxidants, are chemical substances that can delay the oxidation and aging of polymers. When only a small amount of them exists in a polymer system, they can delay or inhibit the oxidation process of the polymer, thereby preventing the aging of the polymer and extending its service life. Therefore, they are widely used in rubber, plastics, chemical fiber polymer materials, chemical industry and food processing.

[0037] The antioxidant selected in the embodiment of the present invention has the characteristics of low volatility and good compatibility with POK resin. In addition, when selecting an antioxidant, it is also necessary to consider whether the discoloration and pollution performance of the product after the introduction of the antioxidant meets the requirements of the product application, as well as the impact on the processing performance.

[0038] In an optional embodiment of the present invention, the anti-UV agent is selected from at least one of UV234, UV770, UV360, UV1577 and UV1164.

[0039] Anti-UV agents, also known as antioxidants, are substances that can delay the aging of polymer compounds. They extend the service life of products mainly by inhibiting oxidation, heat or light. The anti-UV agent used in the present invention is mainly an anti-ultraviolet agent, which mainly protects the product from damage by reflecting, scattering or absorbing ultraviolet rays.

[0040] In an optional embodiment of the present invention, the lubricant is selected from at least one of zinc stearate, calcium stearate, pentaerythritol stearate, ethylene bisstearamide, TAF, silicone powder, talc, and OP wax.

[0041] It should be noted that the main mechanism of action of lubricants is to improve the friction of the polymer melt surface, reduce melt viscosity, enhance fluidity, and act as a melt promoter, anti-adhesion and antistatic agent, and slip agent. The role of lubricants in the processing of polymer materials is crucial. First of all, lubricants can reduce the friction of polymer materials in a molten state, which helps to improve the fluidity of the material and prevent surface roughness. By reducing the friction between polymer molecules, lubricants reduce the viscosity of the melt, making the material smoother when passing through narrow slits, gates and other flow channels of processing machinery. In addition, lubricants can also act as melt promoters to accelerate the plasticization process of polymer materials.

[0042] Furthermore, the lubricant used in the embodiment of the present invention is silicone powder, which has the characteristics of no precipitation and no slipping during extrusion in the screw; in addition, it can also improve the wear resistance and scratch resistance of the product. In other embodiments of the present invention, the type of lubricant can be reasonably adjusted according to actual needs.

[0043] In an optional embodiment of the present invention, the heat stabilizer is selected from any one of tricalcium phosphate or calcium zeolite powder.

[0044] It should be noted that the role of heat stabilizers in polymers is mainly to prevent polymers from being degraded due to heat and mechanical shearing during processing and use, thereby extending the service life of the product. The present invention introduces a heat stabilizer in the preparation process of the POK material, which has affinity for the polymer material, is non-toxic or low-toxic, and does not react with existing materials in the polymer material. It can significantly improve the thermal stability of the polymer material, prevent it from being degraded under the action of heat, oxygen, light and other factors, and maintain the physical appearance and working characteristics of the material.

[0045] Specifically, the specifications of tricalcium phosphate selected in the embodiment of the present invention are: tricalcium phosphate content should be >97%, wherein the iron content is ≤20‰; the specifications of calcium zeolite powder are: calcium content should be ≥3%, particle size is 100 mesh-120 mesh, and ammonia absorption value is 100mmol / 100g. In other embodiments of the present invention, the type and specification of the heat stabilizer can be reasonably adjusted according to actual needs.

[0046] In addition, the heat stabilizer needs to be dehydrated before use. Specifically, in the embodiment of the present invention, it is baked at 90° C. for 4 h to 8 h to remove moisture. In other embodiments of the present invention, the operation and time of removing moisture from the heat stabilizer can be reasonably adjusted according to actual needs.

[0047] Furthermore, the heat stabilizer used in the embodiment of the present invention is tricalcium phosphate, which has good chemical stability and heat resistance due to its stable lattice structure.

[0048] In an optional embodiment of the present invention, the flatness ratio of the flat glass fiber is 1:(2-5), the diameter is 5 μm-15 μm, and the short cut length is 1 mm-5 mm.

[0049] Furthermore, the flatness ratio of the flat glass fiber is 1:4, the glass fiber diameter is 10 μm, the short cut length is 3 mm, and there is no surface treatment agent.

[0050] In a second aspect, an embodiment of the present invention provides a method for preparing the aforementioned low-warpage POK material, the preparation method comprising:

[0051] POK resin, coupling agent, antioxidant, anti-UV agent, lubricant and heat stabilizer are mixed in a mixer at a reaction temperature of 40° C. to 80° C. for a reaction time of 1 min to 60 min to obtain a first blend;

[0052] The first blend, glass fiber and mineral filler are fed into a twin-screw extruder from a feeding port. The temperature of the twin-screw extruder is 100° C.-250° C. and the rotation speed is 250 rpm-400 rpm. After melt mixing, the mixture is extruded, pelletized and dried to obtain a low-warpage POK material.

[0053] Specifically, the first blend is put into the main feed of the extruder, the anti-UV agent, glass fiber and mineral filler are fed separately from the two loss-in-weight scales on the extruder, and then fed through the same side feed below (the extruder has 10 zones in total, and the side feed should be installed in zone 7); the twin-screw extrusion temperature is set to 120°C, 245°C, 245°C, 240°C, 240°C, 240°C, 235°C, 235°C, 235°C, 245°C and 245°C from the feed port to the die, and the main engine speed of the extruder is 300rpm.

[0054] Specifically, the melting point of the POK material used in this embodiment is 220° C., and the temperature of the extruder is preferably set to be 20° C. higher than its melting point. It should be noted that the input position of the material components and the setting of the temperature and speed parameters of the extruder can be reasonably adjusted according to actual needs.

[0055] In an optional embodiment of the present invention, the preparation of the first blend comprises:

[0056] The coupling agent is mixed with ethanol and water to prepare a first mixed liquid for standby use; the POK resin is added into a mixer, and the first mixed liquid is sprayed on the surface of the POK resin for 3-6 times for mixing, the reaction temperature is 40°C-80°C, the reaction time is 1min-20min, and a first intermediate is obtained; an antioxidant, a lubricant and a heat stabilizer are added into the first intermediate for reaction, the reaction temperature is 40°C-80°C, and the reaction time is 1min-20min, and a first blend is obtained.

[0057] It should be noted that the preparation of the first mixed solution is mainly to dissolve and dilute the coupling agent, wherein the coupling agent, ethanol and water are prepared in a volume ratio of 2:7:1. The ethanol added in the preparation of the first mixed solution is anhydrous ethanol, and the water can be any one of pure water, ultrapure water and deionized water according to actual conditions; the proportion of the first mixed solution can be reasonably adjusted according to actual needs, and ethanol can also be adjusted to other alcohol solvents according to actual needs. Since the coupling agent belongs to a silane coupling agent, the addition of ethanol is mainly to increase the speed and efficiency of the coupling agent hydrolysis, because ethanol can reduce the surface tension of the silane coupling agent, making it easier for water to react with the silane coupling agent. At the same time, ethanol can be added to the reaction system as a substitute for other solvents to achieve a better reaction effect.

[0058] Specifically, the POK resin is added to the mixer, and the first mixed liquid is sprayed on the surface of the POK resin for 3-6 times, and the mixer is turned on for mixing; each time the first mixed liquid is sprayed, the POK resin and the first mixed liquid need to be fully mixed and stirred before the next spraying; after the first mixed liquid is completely sprayed, it is necessary to continue stirring and continue to react for a certain period of time, and then the antioxidant, lubricant and thermal stabilizer are added to the first intermediate to react to obtain the first blend. During the entire reaction stage, the reaction temperature is maintained unchanged.

[0059] It should be noted that, for the added antioxidants, lubricants and heat stabilizers, each component needs to be stirred evenly before adding another substance.

[0060] In terms of mass fraction, the usage ratio of the first mixed liquid to the POK resin is (0.1-1): 100; further, the usage ratio of the first mixed liquid to the POK resin is (0.1-0.3): 100. If it is lower than this range, the surface treatment may be incomplete, and if it is higher than this range, it will cause material waste and no effect.

[0061] In a third aspect, an embodiment of the present invention provides the use of the low-warpage POK material as described above or the low-warpage POK material prepared by the preparation method as described above in the preparation of a gearbox housing.

[0062] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0063] Example 1

[0064] This embodiment provides a low-warpage POK material, and the preparation method thereof comprises the following steps:

[0065] Prepare the first mixture:

[0066] The coupling agent (KH-792), ethanol and water were mixed in a volume ratio of 2:7:1 to prepare a first mixed solution for later use.

[0067] Prepare the first blend:

[0068] Weigh the mass of POK resin in proportion, put it into a high-speed mixer, heat the high-speed mixer to 60°C, turn on the high-speed mixer at the same time, and evenly spray the first mixed liquid onto the surface of the POK resin, wherein the dosage ratio of the first mixed liquid to the POK resin is 0.2:100. Stir for 1 minute after each spraying. The first mixed liquid is sprayed in 5 times and stirred for 5 minutes. Then, add antioxidant, lubricant, anti-UV agent, and heat stabilizer in sequence, continue stirring for 5 minutes, and obtain the first blend for standby use.

[0069] Preparation of POK materials:

[0070] The first blend is fed into a twin-screw extruder from the main feed; the mineral and glass fiber are fed into the extruder from the first side feed of zone 5 and the second side feed of zone 7 respectively by weight loss scale, and the twin-screw extrusion temperature is set to 120°C, 245°C, 245°C, 240°C, 240°C, 240°C, 235°C, 235°C, 235°C, 245°C from the feed port to the die, respectively, and the main engine speed of the extruder is 300rpm. After melt mixing, the raw materials are extruded, pelletized and dried to obtain POK material.

[0071] The raw material components used in this example are specifically shown in Table 1.

[0072] Example 2

[0073] This embodiment provides a low warpage POK material, which differs from Embodiment 1 only in that:

[0074] Preparation of the first blend: The amount of coupling agent (KH-792) used was 0.5 parts.

[0075] Example 3

[0076] This embodiment provides a low warpage POK material, which differs from Embodiment 1 only in that:

[0077] Preparation of the first blend: The amount of coupling agent (KH-792) used was 0.3 parts.

[0078] Example 4

[0079] This embodiment provides a low warpage POK material, which differs from Embodiment 1 only in that:

[0080] Preparation of the first blend: the amount of POK M930F in the POK resin is 38.4 parts; the amount of calcium sulfate whisker is 12 parts, and the amount of coupling agent (KH-792) is 0.1 parts.

[0081] Example 5

[0082] This embodiment provides a low warpage POK material, which differs from Embodiment 1 only in that:

[0083] Preparation of the first blend: The coupling agent is KH-550, and its usage is 0.5 parts.

[0084] Example 6

[0085] This embodiment provides a low warpage POK material, which differs from Embodiment 1 only in that:

[0086] Preparation of the first blend: The amount of POK M930F in the POK resin was 39 parts; no heat stabilizer was used.

[0087] Example 7

[0088] This embodiment provides a low warpage POK material, which differs from Embodiment 1 only in that:

[0089] Preparation of the first blend: the amount of POK M930F in the POK resin is 41.4 parts; the amount of calcium sulfate whisker is 9 parts.

[0090] Comparative Example 1

[0091] This embodiment provides a low warpage POK material, which differs from Embodiment 1 only in that:

[0092] Preparation of the first blend: the amount of POK M930F in the POK resin is 51.4 parts; the glass fiber is ordinary chopped glass fiber, and the amount thereof is 30 parts.

[0093] Comparative Example 2

[0094] This embodiment provides a low warpage POK material, which differs from Embodiment 1 only in that:

[0095] Preparation of the first blend: the amount of POK M930F in the POK resin is 30.4 parts; the glass fiber is ordinary chopped glass fiber, and the amount thereof is 30 parts; and the amount of calcium sulfate whisker is 20 parts.

[0096] Table 1

[0097]

[0098]

[0099] It should be noted that “-” in Table 1 indicates that the corresponding component material is not added.

[0100] Test Example 1

[0101] In this test example, dry mechanical property tests and wet mechanical property tests were performed on the low warpage POK materials prepared in Examples 1-7 and Comparative Examples 1-2, wherein the test standard for tensile strength is ISO 527, and the instrument is a universal tensile testing machine; the test standard for impact strength is ISO 180, and the instrument is an impact testing machine; the test standard for flexural strength and flexural modulus is ISO 178, and the instrument is a universal tensile testing machine; the specific test results are shown in Table 2.

[0102] Test Example 2

[0103] In this test example, other properties of the low warpage POK materials prepared in Examples 1-7 and Comparative Examples 1-2 were tested, among which the water absorption rate was tested by ISO 62; the molding shrinkage was tested by an internal method; the melt index was tested by ASTM D1238; the surface resistivity was tested by ASTM D257; the ΔE after 48h xenon lamp aging was tested by a light power of 0.51W / (m 2 · nm)@340nm, temperature 63℃, humidity 90%; color test, the specific test method is visual; warpage test, the specific test method is internal method; relevant test results are shown in Table 2.

[0104] Table 2

[0105]

[0106]

[0107] It can be concluded from Table 2 that the mechanical properties analysis is as follows: in the dry state, the tensile strength of the embodiments is generally higher, among which embodiments 1, 5, and 6 are particularly outstanding; the notched impact strength and flexural strength also show similar trends, and the differences between the embodiments are relatively small; the mechanical properties in the wet state are generally lower than those in the dry state, but the relative rankings between the embodiments remain consistent.

[0108] Other performance analysis: The water absorption rate and molding shrinkage rate are not much different among the embodiments, and are maintained at a low level; the data of melt index and surface resistivity are relatively stable, without significant fluctuations; the △E value after 48 hours of xenon lamp aging shows that the color stability of embodiments 1 to 5 is good, while the color changes of the comparative examples and some embodiments (such as embodiments 6 and 7) are large.

[0109] Color and warpage: The material color is mainly light yellow, the color of Example 7 is obviously dark yellow, and the color of Comparative Example 2 is a mixture of yellow and green. The warpage data show that the degree of warpage between the examples is not much different, but the comparative examples and some examples (such as Example 7, Comparative Examples 1 and 2) have higher warpage.

[0110] As described above, Examples 1, 5, and 6 of the present invention have excellent mechanical properties and have high tensile strength, notched impact strength, and flexural strength. The wet mechanical properties are generally lower than those in the dry state, but the relative performance differences between the examples remain consistent. The color stability and warpage of the material are also important indicators for evaluating its performance, and Example 1 has a better overall performance.

[0111] In summary, the low-warpage POK material prepared by the present invention has excellent mechanical properties, low water absorption, low warpage and super excellent wear resistance. Specifically, in the POK material system, a composite ratio of special-shaped flat glass fiber and calcium sulfate whisker is added, and the material with the lowest warpage is obtained by adjusting the ratio of flat glass fiber to mineral. On the basis of not destroying the original wear resistance, chemical resistance and hydrolysis resistance of POK, the comprehensive performance and anti-warpage performance of POK are greatly improved; for plastic products, a warpage of less than 0.2% can ensure that the product has good dimensional stability after molding; the addition of silane coupling agent improves the interface bonding ability of POK and glass fiber / mineral whisker, so that its comprehensive mechanical properties are further improved; Example 7 increases the addition amount of calcium sulfate whisker, resulting in serious whisker agglomeration on the surface of the product, affecting the comprehensive mechanical properties. When the addition amount of calcium sulfate whisker is between 12% and 17%, the anti-warpage effect of POK material is the best; at the same time, because the carbonyl group of POK itself is relatively active, the addition of tricalcium phosphate further improves the color stability of POK, which can ensure better processing performance and color stability of the final product. The preparation method is simple and easy to operate, and the preparation cost is low, and is suitable for promotion in the preparation of gear box housings for cleaning household appliances.

[0112] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A low warpage POK material, characterized in that: The low warpage POK material comprises the following components by mass: POK resin 40-64 parts, coupling agent 0.1-0.5 parts, antioxidant 0.05-0.5 parts, lubricant 0.5-5 parts, heat stabilizer 0.01-5 parts, glass fiber 29-31 parts, mineral filler 9-20 parts, anti-UV agent 0.5-1 parts; The glass fibers include flat glass fibers; and the mineral filler includes calcium sulfate whiskers.

2. The low warpage POK material according to claim 1, characterized in that: The POK resin is a mixed resin; the POK resin includes a high-viscosity resin and a low-viscosity resin in a mass ratio of 1:(1.5-2); Preferably, the POK resin comprises a high viscosity resin and a low viscosity resin in a mass ratio of 1:(1.7-2); Preferably, the molecular weight of the high viscosity resin is 170,000-190,000, and the molecular weight of the low viscosity resin is 120,000-140,000.

3. The low warpage POK material according to claim 1, characterized in that: The coupling agent is selected from any one of N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane and γ-aminopropyltriethoxysilane.

4. The low warpage POK material according to claim 1, characterized in that: The antioxidant is selected from at least one of antioxidant 1010, antioxidant 1098, antioxidant 168, antioxidant 9228, antioxidant 2450, antioxidant AO-80 and MD-697; Preferably, the antioxidant comprises antioxidant 1010 and antioxidant 168 in a mass ratio of 1:

2.

5. The low warpage POK material according to claim 1, characterized in that: The anti-UV agent is selected from at least one of UV234, UV770, UV360, UV1577 and UV1164.

6. The low warpage POK material according to claim 1, characterized in that: The lubricant is selected from at least one of zinc stearate, calcium stearate, pentaerythritol stearate, ethylene bis stearamide, TAF, silicone powder, talc, and OP wax; Preferably, the heat stabilizer is selected from any one of tricalcium phosphate or calcium zeolite powder.

7. The low warpage POK material according to claim 1, characterized in that: The flatness ratio of the flat glass fiber is 1:(3-4), the diameter is 5 μm-15 μm, and the short cut length is 1 mm-5 mm.

8. A method for preparing a low-warpage POK material according to any one of claims 1 to 7, characterized in that: The preparation method comprises: POK resin, coupling agent, antioxidant, anti-UV agent, lubricant and heat stabilizer are mixed in a mixer at a reaction temperature of 40° C. to 80° C. for a reaction time of 1 min to 60 min to obtain a first blend; The first blend, glass fiber and mineral filler are fed into a twin-screw extruder from a feeding port. The temperature of the twin-screw extruder is 100° C.-250° C. and the rotation speed is 250 rpm-400 rpm. After melt mixing, the low-warpage POK material is obtained by extrusion, pelletizing and drying.

9. The preparation method according to claim 8, characterized in that: The preparation of the first blend comprises: Mixing the coupling agent with ethanol and water to prepare a first mixed solution for standby use; Add the POK resin into a mixer, spray the first mixed solution on the surface of the POK resin 3-6 times, perform mixing treatment, the reaction temperature is 40° C.-80° C., the reaction time is 1 min-20 min, and the first intermediate is obtained; Adding an antioxidant, a lubricant and a heat stabilizer to the first intermediate to react at a reaction temperature of 40° C. to 80° C. for a reaction time of 1 min to 20 min to obtain the first blend; Preferably, the ratio of the first mixed liquid to the POK resin is (0.1-1):100, more preferably (0.1-0.3):100, in terms of mass fractions.

10. Use of the low-warpage POK material according to any one of claims 1 to 7 or the low-warpage POK material prepared by the preparation method according to any one of claims 8 to 9 in preparing a gearbox housing.

Citation Information

Cited By

  • Special low-warpage polyketone wire for 3D printing and preparation method of special low-warpage polyketone wire

    CN122465346A